Novel GM-CSF-based vaccines: One small step in GM-CSF gene optimization, one giant leap for human vaccines - Yu, Ting-Wei (Hum Vaccin Immunother, 2016)
Granulocyte macrophage-colony stimulating factor (GM-CSF) is a potent immunomodulatory cytokine that is known to facilitate vaccine efficacy by promoting the development and prolongation of both humoral and cellular immunity. In the past years we have generated a novel codon-optimized GM-CSF gene as an adjuvant. The codon-optimized GM-CSF gene significantly increased protein expression levels in all cells tested and helped in generating a strong immune responses against HIV-1 Gag and HPV-associated cancer. Here, we review the literature dealing with the adjuvant activity of GM-CSF both in animal models and clinical trials. We anticipate that the codon-optimized GM-CSF gene offers a practical molecular strategy for potentiating immune responses to tumor cell-based vaccinations as well as other immunotherapeutic strategies.